Socio-cultural dimensions and impact Of the pavvurulun festival Of tuguegarao city, philippines - BAYANI, JAY-R B. (International Journal of Psychosocial Rehabilitation, 2020)
Festivals are one of the fastest growing forms of tourism. Festivals are rapidly They are becoming increasingly popular in rural areas as a means to revitalize local economies. The study aimed to identify the socio- economic dimensions and impacts of Pavvurulun Festival of Tuguegarao City, Philippines.The Pav-vurulun festival is an annual event in Tuguegarao City that commemorates patronal fiesta. This is a week-long celebration in honor of St. Hyacinth. Pav-vurulun connotes coming together which allows members of the community to gather together and are enjoin to celebrate prestigious events.This study generally aimed to identify the socio-cultural dimensions and impact of Pav-vurulunan Festival of Tuguegarao City. The festival have direct and indirect social, environmental and political and environmental impacts in the community. The benefits are intrinsic and extrinsic and had a large impact on the community’s growth and development. Interestingly, it showed that they consider that when the community benefits from the festival, they as members of the community also do. the The study pointed out that women dominated the participation in the said festival and most are youths. There were direct and indirect impacts on the community through the opportunities they provide for such as participation, skills development and volunteering.It showed that most of the respondents belong to the female group and are young adults. The youths were also more exposed to the festival. The organizers were mostly volunteers and few of them were hired and received compensation in exchange of their services. Since most are voluntary, the organizing committee members believe that they truly benefited from the festival.Possibly, new ideas and programs suited to the changing needs of the society is also recommended. Although, the study revealed an increased awareness of the culture, history and tradition of Tuguegarao City made possible by the festival, organizers must intensify their mechanisms on using the digital media in promoting festival and more programs and festivities must be displayed.